Susceptibility tests to second line drugs and re-treatment of tuberculosis revisiting early experiences - de Kantor, Isabel N. (2007)
Fil: de Kantor, Isabel N. Organización Mundial de la Salud (OMS). Panel de Consultores en Tuberculosis, Buenos Aires; Argentina.